2020
DOI: 10.1016/j.lungcan.2019.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy rechallenge after nivolumab treatment in advanced non-small cell lung cancer in the real-world setting: A national data base analysis

Abstract: Nivolumab is now a reference treatment for patients with advanced non-small cell lung cancer (NSCLC) after failure of prior platinum-based chemotherapy. Little data are available on treatment approaches following discontinuation of nivolumab and on the interest of a second course of immunotherapy after nivolumab discontinuation. The aims of this study were to describe treatment pathways following nivolumab discontinuation and to describe survival following retreatment with immunotherapy. Materials and methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 38 publications
2
75
1
Order By: Relevance
“…Despite broader inclusion criteria used in EVIDENS, these effectiveness results are in line with those of the CheckMate 017 7 and 057 6 phase III trials and other real-world studies of nivolumab conducted in Europe ( Table 5). [15][16][17][18][19][20][21][22][23][24][25][26][27] Examination of the influence of baseline characteristics on OS did not reveal any significant effect of PD-L1 expression, although the analysis may have been underpowered to detect an association given that the sample size of patients in whom PD-L1 expression data were available was small. ECOG PS, smoking status, corticosteroids at baseline, EGFR mutation status, symptomatic brain metastasis and TRAEs significantly influenced OS in nivolumab recipients as seen in our multivariate analysis, even though some of these factors are also well-known prognostic factors in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite broader inclusion criteria used in EVIDENS, these effectiveness results are in line with those of the CheckMate 017 7 and 057 6 phase III trials and other real-world studies of nivolumab conducted in Europe ( Table 5). [15][16][17][18][19][20][21][22][23][24][25][26][27] Examination of the influence of baseline characteristics on OS did not reveal any significant effect of PD-L1 expression, although the analysis may have been underpowered to detect an association given that the sample size of patients in whom PD-L1 expression data were available was small. ECOG PS, smoking status, corticosteroids at baseline, EGFR mutation status, symptomatic brain metastasis and TRAEs significantly influenced OS in nivolumab recipients as seen in our multivariate analysis, even though some of these factors are also well-known prognostic factors in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…13 Instead, data have been reported from small patient cohorts, retrospective studies and early access programs, for which inclusion/exclusion enrollment criteria may be restrictive. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Due to known variation in cancer survival rates across Europe, 28 country-specific data may be more appropriate to describe the real-world experience with nivolumab in the treatment of NSCLC. Furthermore, data collected in the context of a real-world study can also help to address important clinical evidence gaps such as the outcomes in patients who were underrepresented in, or excluded from, pivotal clinical trials of nivolumab due to more severe comorbidities or poor prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…OS in the retreatment situation significantly correlated with duration of initial IO exposure, which may be due to a time-dependent consolidation of an immune memory. The median OS for IO retreatment was above 12 months, which compares favorably with OS during initial nivolumab treatment or with standard third-line chemotherapy in advanced NSCLC [ 70 ]. Moreover, the phase III KEYNOTE-024 trial demonstrated the feasibility of a second course pembrolizumab in 10 NSCLC patients who had progressed after completion of 2 year pembrolizumab monotherapy, with an objective response rate (ORR) in 7/10 patients [ 71 ].…”
Section: Future Io Treatment Strategiesmentioning
confidence: 99%
“…The long-term response to immunotherapy may be related to the duration of, or reaction to, treatment. Levra et al 32 conducted a study of challenge immunotherapy after nivolumab therapy for advanced NSCLC in the realworld setting. The results indicated that patients with longer initial nivolumab treatment had a higher survival rate after retreatment.…”
Section: Discussionmentioning
confidence: 99%